PENGARUH E-MARKETING MIX TERHADAP IMPULSE BUYING MELALUI HEDONIC SHOPPING SEBAGAI VARIABEL INTERVENING (Pendekatan Analisis Jalur/Path Analysis padaPlatform TikTok Sho) - Junjun Arip Nugraha; Medira Abdillah (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2023)
The purpose of this study is to determine the effect of e-marketing mix on impulse buying through hedonicshopping as an intervening variable (study on the Tiktok platform). The method used in this research isquantitative research. The population in this study are Tiktok users. The sampling technique used theAccidental Sampling technique and obtained a sample of 96 respondents. Data collection using the datamethod in the form of a questionnaire and data processing using the SPSS version 25. The analysis toolused was path analysis, using the T test and F test and the coefficient of determination. The results of theanalysis show that the product variable (X1) has no significant effect on impulse buying (Y) with a betavalue of 0.091, promotion (X2) has no significant effect on impulse buying (Y) with a beta value of 0.028,place (X3) has no negative effect significant effect on impulse buying (Y) with a beta value of -0.053, price(X4) has no significant negative effect on impulse buying (Y) with a beta value of -0.097, personalization(X5) has no significant effect on impulse buying (Y) with beta value of 0.152, privacy (X6) has no significanteffect on impulse buying (Y) with a beta value of 0.264, Customer Service (X7) has a significant effect onimpulse buying (Y) with a beta value of 0.501, Community (X8) has an effect no significant negative effecton impulse buying (Y) with a beta value of -0.208, Site (X9) has no significant negative effect on impulsebuying (Y) with a beta value of -0.049, Security (X10) has no significant negative effect on impulse buyingbuying (Y) with a beta value of -0.053, Sales Promotion (X11) has no significant effect on impulse buying(Y) with a beta value of 0.067